Dental and jaw injuries sustained by hooligans. Issue 6 (15th July 2015) - Sekulic, Michel; Kühl, Sebastian; Connert, Thomas; Krastl, Gabriel; Filippi, Andreas
Abstract: Aim: The study deals with fighting‐related dental injuries sustained by hooligans and the influence of wearing a mouthguard on fighting‐related dental trauma. Material and Methods: From 2012 to 2013, standardized multiple‐choice questionnaires were distributed via contacts in the hooligan scene in Switzerland. The survey was conducted with the guarantee of complete anonymity and investigated injury patterns in hooligans from different age groups, of different nationalities as well as educational and income levels. Results: Of the 95 hooligans surveyed, 82 had sustained a dental injury: 29 were minor and 53 were severe dental injuries. During violent confrontations, 37 of the 95 hooligans wore a mouthguard. The most commonly used mouthguards were custom‐made (19/37) or boil‐and‐bite (10/37). The use of ready‐made mouthguards without an individualized fit (6/37) was less frequent. Hooligans who wore a boil‐and‐bite or a custom‐made mouthguard lost fewer teeth during fights than participants wearing a mouthguard without an individualized fit ( P  = 0.056). Conclusion: The risk of trauma during violent confrontations between hooligans is very high, as expected. The injuries range from dental trauma to bruising, lacerations and even serious bone fractures of the face and the extremities. During violent clashes over a third of the hooligans wear a mouthguard that has usually been custom‐made or at least individually fitted; this is a far higher frequency than for most contact sports.